Evaluation of the Therapeutic Effect of Antibiotics on Scrub Typhus: A Systematic Review and Network Meta-Analysis - Lu, Dafeng; Wang, Taiwu; Luo, Zhenghan; Ye, Fuqiang; Qian, Jiaojiao; Zhang, Jinhai; Wang, Chunhui (Frontiers in Public Health, 2022)
Background To explore the efficacy and safety of drugs in patients with scrub typhus. Methods For this systematic review and network meta-analysis, we searched PubMed, Embase, Web of Science, Cochrane Central Register of Clinical Trials, China National Knowledge Infrastructure (CNKI), and Wanfang data (WF) up to December 2021. All randomized controlled trials (RCTs) of antibiotics used to treat scrub typhus were included without language or date restrictions. The overall effectiveness was evaluated from 4 perspectives: cure rate (CR), defervescence time (DT), gastrointestinal symptoms–adverse events (GS-AD), and abnormal blood count–adverse events (ABC-AD). The quality of evidence was evaluated using the Cochrane Risk of Bias tool and GRADE system. Results Sixteen studies involving 1,582 patients were included to evaluate 7 drugs, namely, azithromycin, doxycycline, chloramphenicol, tetracycline, rifampin, moxifloxacin, and telithromycin. In this network meta-analysis, rifampicin (82%) and chloramphenicol (65%) were more effective in terms of CR, and moxifloxacin (3%) from the quinolone family was the worst. Azithromycin caused the fewest events in terms of ABC-AD. No differences were found in this network meta-analysis (NMA) in terms of DT and GS-AD. Conclusions Rifampicin was associated with the highest CR benefit and the lowest risk of DT when used to treat patients with scrub typhus, except in areas where tuberculosis (TB) was endemic. Azithromycin was found to be better in CR and was associated with a lower probability of GS-AD and ABC-AD; therefore, it may be considered to treat pregnant women and children. Moxifloxacin had a much lower CR than other drugs and is, therefore, not recommended for the management of scrub typhus. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/, identifier: CRD42021287837.